PENGARUH PENERAPAN MEDIA PUZZLE DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS II SDN 19 SITIUNG - Amar Salahuddin; Estuhono; Rhizka Darmastuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of second-grade students in Indonesian language subjects, particularly in reading skills at SD Negeri 19 Sitiung. This condition was caused by the limited use of varied learning media, resulting in low student participation and motivation during the learning process. Puzzle media was selected as an alternative instructional medium because it can create a more engaging, interactive, and enjoyable learning environment. This study aimed to determine the effect of using puzzle media on students' learning outcomes in the Indonesian language subject for second-grade students at SD Negeri 19 Sitiung. The research employed a quantitative approach using a Pre-Experimental Design with a One Group Pretest–Posttest Design. The sample consisted of 24 second-grade students selected through a saturated sampling technique. The research instrument was a 25-item multiple-choice achievement test that had met the requirements of validity, reliability, item difficulty, and discrimination index. Data were analyzed using the Shapiro–Wilk normality test and the Paired Sample t-test with the assistance of SPSS version 25. The findings revealed that the mean pretest score increased from 61,67 to 79,17 on the posttest, indicating an improvement of 17,50 points. The hypothesis testing also showed that the use of puzzle media had a significant effect on students' learning outcomes. Therefore, puzzle media is considered an effective and innovative learning medium for improving students' learning outcomes in Indonesian language learning at the elementary school level.